Aluminum nitride sintered body and electronic component
By adding yttrium oxide as a sintering aid to the aluminum-boron compound ceramic body and using a heat treatment method embedded in aluminum-boron compound powder, the dual demand for improved thermal conductivity and insulation performance in electronic components is solved, and a high thermal conductivity and high electrical insulation aluminum-boron compound ceramic body is achieved.
Patent Information
- Application Number
- JP2025014532
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-01-31
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2043-08-29
AI Technical Summary
In electronic components, with the further miniaturization of the circuit, the thermal conductivity and insulation performance of aluminum-boron compound ceramic bodies need to be further improved to meet the dual needs of high heat dissipation and high electrical insulation.
By adding aluminum-boron compound particles and yttrium oxide as sintering aid to the aluminum-boron compound ceramic body, and heat treatment is carried out by inserting aluminum-boron compound powder, an aluminum-boron compound ceramic body with high thermal conductivity and high electrical insulation properties is formed.
The high thermal conductivity (240 W/mK or higher) and high electrical insulation properties (20 kV/mm or higher) of aluminum-boron compound ceramic bodies are achieved, while the sintering additive and carbon content are controlled, ensuring high mechanical strength and low dead power loss of the ceramic bodies.
Smart Images

Figure 2025069291000004 
Figure 2025069291000005 
Figure 2025069291000006
Abstract
Description
[Technical field]
[0001] The present invention relates to an aluminum nitride sintered body, a method for producing the same, and an electronic device. [Background technology]
[0002] Aluminum nitride sintered products are made of insulating materials with high thermal conductivity and have been attracting attention as materials for high thermal conductive substrates. Due to their excellent thermal conductivity, the aluminum nitride sintered products are widely used as heat dissipation substrates for electronic components such as power transistor module substrates, light emitting diodes, IC packages, and laser diodes in semiconductors and electronic devices whose operation becomes unstable under high heat. In recent years, aluminum nitride sintered substrates have been widely used in electronic substrates for mobile applications, and higher heat dissipation properties are required. Therefore, various attempts have been made to improve the thermal conductivity of aluminum nitride sintered substrates.
[0003] For example, Patent Document 1 discloses an aluminum nitride sintered body and a method for producing the same. The aluminum nitride sintered body in Patent Document 1 has a high thermal conductivity of 260 W / m K or more by specifying the constituent components and content ratio of the grain boundary phase and the microstructure, specifically the average diameter, minimum diameter, maximum diameter, and number of aluminum nitride crystal grains. This method for producing an aluminum nitride sintered body is characterized by comprising a molding step of mixing aluminum nitride powder having an average particle size of 1.5 μm or less with a sintering aid containing at least a Y compound powder, and molding the mixture to obtain a molded body, a degreasing step of degreasing the molded body, a deoxidizing step of heat-treating the deoxidized molded body in a non-oxidizing atmosphere or a reduced pressure atmosphere at 1300°C to 1550°C to deoxidize it, a sintering step of heat-treating the deoxidized molded body in a non-oxidizing atmosphere at 1800°C to 1950°C to obtain a primary sintered body having a thermal conductivity of 230 W / m·K or more, and a reduction step of heat-treating the primary sintered body in a weakly reducing atmosphere at 1750°C to 1900°C to obtain a high thermal conductive aluminum nitride sintered body having a thermal conductivity of 260 W / m·K or more. In particular, in the sintering step, the deoxidized molded body is heat-treated in a non-oxidizing atmosphere at 1800°C to 1950°C to obtain a primary sintered body having a thermal conductivity of 230 W / m·K or more. In the subsequent reduction process, the primary sintered body is heat treated in a weakly reducing atmosphere at 1750°C to 1900°C to obtain an aluminum nitride sintered body with a thermal conductivity of 260 W / m K or more (high thermal conductive aluminum nitride sintered body). In this reduction process, the grain boundary phase, which is a factor that inhibits thermal conductivity, is precipitated on the surface and removed, resulting in an aluminum nitride sintered body with a thermal conductivity of 260 W / m K or more. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2011-37691 A Summary of the Invention [Problem to be solved by the invention]
[0005] Patent Document 1 provides an aluminum nitride sintered body having high thermal conductivity. Meanwhile, in recent years, due to further miniaturization of electronic circuits, the distance between conductors in a circuit pattern on an aluminum nitride sintered body substrate has become smaller and smaller, and the electrical properties of the aluminum nitride sintered body as an insulator have also become important. Therefore, the inventors set out to improve the insulating performance of the aluminum nitride sintered body while maintaining its high thermal conductivity.
[0006] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide an aluminum nitride sintered body having both high thermal conductivity characteristics and high insulating performance, and a method for manufacturing the same. [Means for solving the problem]
[0007] An aluminum nitride sintered body according to one embodiment of the present invention is an aluminum nitride sintered body including aluminum nitride particles and a sintering aid phase, The thermal conductivity is 240 W / mK or more and the dielectric strength is 20 kV / mm or more when converted to a thickness of 2.5 mm. The thermal conductivity is more preferably 260 W / mK or more. The dielectric strength is more preferably 23 kV / mm or more, and even more preferably 29 kV / mm or more.
[0008] The aluminum nitride sintered body according to a further embodiment of the present invention more preferably has a volume resistivity of 5.0×10 13 It is characterized by a resistance of Ω·cm or more.
[0009] An aluminum nitride sintered body according to a further embodiment of the present invention is more preferably characterized in that the Y2O3 content in the sintered body is 0.1% by weight or less and the carbon content in the sintered body is 0.05% by weight or less.
[0010] An aluminum nitride sintered body according to a further embodiment of the present invention is more preferably characterized in that the relative dielectric constant is 8.5 or less and the dielectric loss tangent is 0.001 or less.
[0011] In a further embodiment of the present invention, the aluminum nitride sintered body is more preferably a substrate of the aluminum nitride sintered body, the substrate being characterized by an average value of lightness measured at one point in the center and four points at the corners, L * It is characterized by a value of 57 or greater.
[0012] An aluminum nitride sintered body according to a further embodiment of the present invention is more preferably characterized by being obtained by sintering 90 to 99.5% by weight of aluminum nitride and 0.5 to 10% by weight of yttrium oxide.
[0013] An aluminum nitride sintered body according to one embodiment of the present invention is an aluminum nitride sintered body including aluminum nitride particles and a sintering aid phase, The thermal conductivity when converted to a thickness of 2.5 mm is 240 W / mK or more, and the volume resistivity is 5.0 x 10 13 It is characterized in that the thermal conductivity is Ω·cm or more. It is more preferable that the thermal conductivity is 260 W / mK or more.
[0014] An aluminum nitride sintered body according to one embodiment of the present invention is an aluminum nitride sintered body including aluminum nitride particles and a sintering aid phase, The thermal conductivity when converted to a thickness of 2.5 mm is 240 W / mK or more, and the L value indicates the average value of the brightness measured at one point in the center and four points on the corners of the aluminum nitride sintered body substrate. * The thermal conductivity is preferably 260 W / mK or more.
[0015] An aluminum nitride sintered body according to one embodiment of the present invention is an aluminum nitride sintered body including aluminum nitride particles and a sintering aid phase, The dielectric strength is 20 kV / mm or more, and the average value of the brightness measured at one point in the center and four points on the corners of the aluminum nitride sintered body substrate is L. * It is characterized in that the value is not less than 57. The dielectric strength voltage is more preferably not less than 23 kV / mm, and further preferably not less than 29 kV / mm.
[0016] An aluminum nitride sintered body according to one embodiment of the present invention is an aluminum nitride sintered body including aluminum nitride particles and a sintering aid phase, Volume resistivity is 5.0×10 13 Ω·cm or more, and the average value of the lightness measured at one point in the center and four points on the corners of the aluminum nitride sintered body substrate is L * It is characterized by a value of 57 or greater.
[0017] A method for producing an aluminum nitride sintered body according to one embodiment of the present invention includes the steps of: A mixing step of mixing an aluminum nitride raw material powder, a sintering aid, and an organic solvent to prepare a raw material mixture slurry; a molding step of molding the raw material mixture to obtain a molded body; a degreasing step of heating the molded body in a degreasing temperature range under a dry air inflow or a nitrogen atmosphere to perform a degreasing treatment; a deoxidation step of heating the degreased molded body in a deoxidation temperature range in a nitrogen atmosphere to perform a deoxidation treatment; a sintering step of sintering the deoxidized compact in a nitrogen atmosphere within a sintering temperature range to produce an aluminum nitride precursor sintered body; a reduction firing process in which an embedded structure is prepared by embedding at least a portion of the aluminum nitride precursor sintered body in aluminum nitride powder, and the embedded structure is heat-treated at 1850 to 1950°C in a weakly reducing atmosphere; a removing step of removing the aluminum nitride powder from the reduction-sintered embedded structure to obtain an aluminum nitride sintered body; The present invention is characterized by comprising:
[0018] A further embodiment of the method for producing an aluminum nitride sintered body according to the present invention is more preferably characterized in that the sintering aid is 0.5 to 10% by weight of Y2O3.
[0019] A further embodiment of the method for producing an aluminum nitride sintered body according to the present invention is more preferably characterized in that the reduction and firing step includes placing the aluminum nitride precursor sintered body in a graphite container, or a BN container or an AlN container in which carbon black or a carbon sheet has been placed, and embedding the aluminum nitride precursor sintered body in aluminum nitride powder until it can no longer be seen.
[0020] An electronic component according to one embodiment of the present invention is characterized by comprising the aluminum nitride sintered body and a laser diode mounted on a surface of the aluminum nitride sintered body. Effect of the Invention
[0021] The present invention provides an aluminum nitride sintered body having a high thermal conductivity of 240 W / mK or more and improved insulating performance. [Brief description of the drawings]
[0022] [Figure 1] FIG. 2 is a schematic diagram showing an example of a reduction firing step in one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing an example of a reduction firing step in conventional examples (Comparative Examples 1 and 2). [Diagram 3] 1 is a graph showing the relationship between the lightness L* value and the dielectric strength voltage of aluminum nitride sintered bodies (Examples 1 to 20 and Comparative Examples 1 to 6). [Figure 4] FIG. 1 is a schematic diagram showing an electronic component according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] The aluminum nitride sintered body according to one embodiment of the present invention has a substrate shape with a predetermined thickness and can be used as a circuit board for mounting electronic components. The aluminum nitride sintered body is made by sintering 90 to 99.5% by weight of aluminum nitride and 0.5 to 10% by weight of a sintering aid as main raw materials. The aluminum nitride sintered body is composed of a crystal phase of aluminum nitride particles and a liquid phase composed of a sintering aid phase.
[0024] The sintering aid may be selected from the group consisting of oxides of rare earth elements Y, La, Ce, Pr, Nd, Sm, Gd, Dy, Ho, Er, and Yb. In this embodiment, yttrium oxide (Y2O3) is used as the sintering aid. It is known that the addition of rare earth oxides as sintering aids can lower the liquid phase formation temperature during sintering and densify the crystal structure, resulting in a material that has both relatively high thermal conductivity and mechanical strength.
[0025] The aluminum nitride sintered body of this embodiment is characterized in that the Y2O3 content remaining in the sintered body is 0.1 wt% or less, and the carbon (C element) content remaining in the sintered body is 0.05 wt% or less. It is more preferable that the Y2O3 content is 0.03 wt% or less. It is also more preferable that the carbon content is 0.03 wt% or less. The aluminum nitride sintered body of the present invention achieves both high thermal conductivity and high electrical properties as an insulator by controlling both the Y2O3 content and the carbon content remaining in the sintered body.
[0026] The aluminum nitride sintered body of this embodiment has a thermal conductivity characteristic of 240 W / mK or more when converted into a thickness of 2.5 mm. The thermal conductivity is preferably 260 W / mK or more, and more preferably 265 W / mK or more. In addition to high thermal conductivity, the aluminum nitride sintered body has the following electrical characteristics as an insulator. The aluminum nitride sintered body is preferably characterized by a dielectric strength voltage of 20 kV / mm or more. The dielectric strength voltage is more preferably 23 kV / mm or more, and even more preferably 29 kV / mm or more. The dielectric strength voltage indicates the upper limit of the voltage that can be applied to an insulator without causing dielectric breakdown, and is an index of the insulating performance of the sintered body. In addition, the aluminum nitride sintered body is preferably characterized by a volume resistivity of 5.0×10 13 Ω cm or more, preferably 7.1×10 13 The aluminum nitride sintered body is characterized by having a dielectric constant of 8.5 or less, preferably 8.3 or less, and a dielectric tangent of 0.001 or less, preferably 0.00086 or less. In other words, the aluminum nitride sintered body of this embodiment has both high thermal conductivity and high insulation performance.
[0027] In addition, the aluminum nitride sintered body has a lightness L that indicates its appearance. * It is characterized by a value of 57 or more. * The value indicates the average value of the lightness measured at one point in the center and four points at the corners of the aluminum nitride sintered body substrate. The aluminum nitride sintered body of this embodiment has a higher lightness than aluminum nitride sintered bodies manufactured by conventional methods. Figure 3 shows the lightness L obtained from the experimental results. * As shown in Figure 3, the correlation between the lightness L and the dielectric strength is shown. * The value and the dielectric strength are directly proportional to each other. *When the value is 0.001, the dielectric strength is 20kV / mm or more. Conventionally, destructive evaluation was performed by sampling to inspect the characteristics of sintered aluminum nitride products. By utilizing this correlation, the lightness L value measured by a color difference meter can be measured. * By measuring the value, it is now possible to sort the entire number of products non-destructively.
[0028] Next, a method for producing an aluminum nitride sintered body according to the present embodiment will be described. The method for producing an aluminum nitride sintered body mainly includes a mixing step of mixing an aluminum nitride raw material powder, a sintering aid, and an organic solvent to produce a slurry of the raw material mixture, a molding step of molding the raw material mixture to obtain a molded body, a degreasing step of heating the molded body in a degreasing temperature range under a dry air inflow or in a nitrogen atmosphere to perform a degreasing treatment, a deoxidizing step of heating the molded body after degreasing in a deoxidizing temperature range in a nitrogen atmosphere to perform a deoxidizing treatment, a sintering step of sintering the molded body after deoxidization in a sintering temperature range in a nitrogen atmosphere to produce an aluminum nitride precursor sintered body, a reduction firing step of embedding the aluminum nitride precursor sintered body with aluminum nitride powder to produce an embedded structure, and heat-treating the embedded structure at 1850 to 1950 ° C. in a weakly reducing atmosphere, and a removal step of removing the aluminum nitride powder from the embedded structure after reduction firing to obtain an aluminum nitride sintered body. Each step will be described in detail below. In this specification, "embedded" does not only mean that the aluminum nitride precursor sintered body is completely covered with aluminum nitride powder (the outer peripheral surface of the aluminum nitride precursor sintered body is completely surrounded by aluminum nitride powder), but also that the majority of the outer peripheral surface of the aluminum nitride precursor sintered body is covered with aluminum nitride powder to the extent that part of the outer peripheral surface is visible.
[0029] In the mixing step, an appropriate amount of aluminum nitride raw material powder and an appropriate amount of sintering aid powder are prepared. The aluminum nitride raw material powder, which is the main raw material, is preferably a high-purity fine powder with few metal impurities and low oxygen content. The sintering aid may be selected from the group of oxides of rare earth elements Y, La, Ce, Pr, Nd, Sm, Gd, Dy, Ho, Er, and Yb, and is preferably Y2O3. In the manufacturing method of this embodiment, 90 to 99.5% by weight of aluminum nitride raw material powder and 0.5 to 10% by weight of Y2O3 are mixed. The prepared raw materials (aluminum nitride and sintering aid) are put into a grinding mixer such as a ball mill, and an organic solvent, a dispersant, an organic binder, and / or a plasticizer are added, and the mixed material is sufficiently ground and mixed for a predetermined time. The organic solvent is, for example, a solvent prepared by mixing toluene and ethanol in a predetermined ratio. The amount of the organic solvent is about 30 to 70 parts by weight based on 100 parts by weight of the aluminum nitride raw material powder. The dispersant is, for example, a polycarboxylic acid surfactant. However, these organic solvents and dispersants can be selected arbitrarily. The organic binder is, for example, polyvinyl butyral resin or acrylic resin. The amount of the binder added is about 3 to 10 parts by weight based on 100 parts by weight of the raw material powder. The plasticizer is, for example, dibutyl phthalate (DBP). The amount of the binder added is about 1 to 5 parts by weight based on 100 parts by weight of the raw material powder. Then, a slurry-like raw material mixture in which each raw material is sufficiently dispersed and mixed is obtained. An additional additive may be added to the mixture of aluminum nitride raw material powder and sintering aid powder.
[0030] In the molding step, the obtained slurry-like raw material mixture is molded into a shape having a predetermined size and thickness by any method such as press molding, casting, or doctor blade molding to produce a molded body.
[0031] In the degreasing step, the molded body is placed in a degreasing oven and heated for about 1 hour or more in a degreasing temperature range under an inflow of dry air or in a nitrogen atmosphere (although not limited to this), thereby removing organic components such as the added organic binder. The degreasing temperature range is preferably about 400 to 600°C (so as not to sinter the molded body). More preferably, the molded body is placed in a case made of BN (boron nitride) and heated for 4 hours at about 500°C under an inflow of dry air or heated for 4 hours at about 600°C in a nitrogen atmosphere, thereby properly degreasing the organic components.
[0032] In the deoxidation step, the degreased molded body is placed in a sintering furnace and heated in a nitrogen atmosphere in a deoxidation temperature range for 10 to 20 hours to deoxidize the molded body. The deoxidation temperature range is preferably 1500 to 1650° C. More preferably, the degreased molded body is placed inside a sealed BN case, and the case is placed in a sintering furnace for heat treatment.
[0033] In the sintering step, the deoxidized compact is heated and sintered in a sintering temperature range in a nitrogen atmosphere for 2 to 20 hours in a sintering furnace to produce an aluminum nitride precursor sintered body. The sintering temperature range is preferably 1750 to 1900°C. More preferably, the deoxidized compact is not removed from the sintering furnace, and the sintering step is carried out continuously. The produced aluminum nitride precursor sintered body is removed from the sintering furnace.
[0034] In the reduction firing step, as shown in FIG. 1, the aluminum nitride precursor sintered body is placed in a graphite (C) container, or a BN container or an AlN container in which carbon black or a carbon sheet is placed, and is completely embedded in aluminum nitride powder until the precursor sintered body is no longer visible, thereby producing an embedded structure made of aluminum nitride powder. At this time, it is preferable that all outer surfaces of the aluminum nitride precursor sintered body are surrounded by aluminum nitride powder. Then, the container containing the embedded structure is sealed, and the container is placed in a firing furnace. The aluminum nitride powder for embedding is preferably a powder with an oxygen content of 1% by weight or less. Thereafter, the material is heated at 1850 to 1950°C for 10 to 100 hours to perform reduction firing. At this time, graphite (carbon) or carbon black functions as a weak reducing atmosphere source, so that the inside of the firing furnace can be made to have a weak reducing atmosphere. Nitrogen gas may be introduced in this reduction firing step. Alternatively, instead of introducing graphite (carbon) or carbon black, CO gas, which is a reducing gas, may be introduced to create a weak reducing atmosphere.
[0035] FIG. 2 is a schematic diagram showing a conventional reduction firing process. In the conventional reduction firing process, an aluminum nitride precursor sintered body is placed in a graphite container and fired in a weakly reducing atmosphere to reduce the aluminum nitride precursor sintered body. As a result, the auxiliary component of the sintering aid is precipitated on the substrate surface and removed from the aluminum nitride precursor sintered body. However, in the conventional reduction firing process, the auxiliary component is discharged only by the atmosphere, which is inefficient, and it has been pointed out that the C component from the graphite container easily flows into the aluminum nitride precursor sintered body. In contrast, in the present invention, as shown in FIG. 1, the aluminum nitride precursor sintered body is embedded in aluminum nitride powder in the reduction firing process, thereby more effectively controlling the discharge amount of the auxiliary component and the inflow amount of the C component, and as a result, both high thermal conductivity and high electrical properties are achieved. In particular, in addition to the discharge of the auxiliary component by controlling the atmosphere, the auxiliary component in the aluminum nitride precursor sintered body is adsorbed by the aluminum nitride powder, which further promotes the discharge of the auxiliary component. In addition, since the aluminum nitride precursor sintered body does not come into direct contact with the graphite container, the intrusion of carbon (C) components from the graphite container is suppressed. Therefore, although the aluminum nitride precursor sintered body is completely covered with aluminum nitride powder in Figure 1, by covering the aluminum nitride precursor sintered body with aluminum nitride powder to the extent that the inflow of carbon (C) components can be suppressed, it is possible to achieve both high thermal conductivity and high electrical properties.
[0036] Finally, in the removal step, the aluminum nitride powder is removed from the embedded structure that has been reduction-sintered, thereby obtaining the aluminum nitride sintered body of the present invention.
[0037] Furthermore, when the aluminum nitride sintered body manufactured by the manufacturing method of this embodiment is identified by crystal phase identification using X-ray diffraction, it may have a diffraction peak of a rare earth compound (e.g., Y2O3, YAM, etc.) serving as a sintering aid in addition to a diffraction peak of the AlN crystal phase.
[0038] The aluminum nitride sintered body of the above embodiment can be used to form an electronic component by mounting a semiconductor element such as a laser diode on its surface. That is, the electronic component of the present invention includes the aluminum nitride sintered body of the above embodiment and a laser diode mounted on the surface of the aluminum nitride sintered body. FIG. 4 is a schematic diagram of an electronic component 10 as an example of an electronic component. As shown in FIG. 4, the electronic component 10 includes an aluminum nitride sintered body substrate 11 and a laser diode (semiconductor element) 13 bonded to one surface of the aluminum nitride sintered body substrate 11 via a conductive film 17. The electronic component 10 further includes a heat sink 15 bonded to the other surface of the aluminum nitride sintered body substrate 11 via the conductive film 17. The conductive film 17 is, for example, an Au film, and is a thin-film circuit formed on the substrate surface by etching. That is, in the electronic component 10, the high thermal conductivity of the aluminum nitride sintered body substrate 11 allows the heat generated by the laser diode 13 to be efficiently conducted to the heat sink 15. Heat from the aluminum nitride sintered body substrate 11 is dissipated in the heat sink 15, effectively suppressing temperature rise in the electronic component 10 or the laser diode 13. Furthermore, in the electronic component 10, the electrical characteristics of the aluminum nitride sintered body substrate 11 effectively suppress damage to the electronic component 10 caused by dielectric breakdown between circuits when a high voltage is applied to the laser diode 13. EXAMPLES
[0039] The present invention will be described in more detail below based on examples and comparative examples, but the present invention should not be construed as being limited to the following examples.
[0040] The aluminum nitride sintered bodies according to Examples 1 to 20 and Comparative Examples 1 to 6 were produced under the following conditions and procedures. Predetermined amounts of aluminum nitride raw material powder and sintering aid powder were prepared. The aluminum nitride raw material powder used was produced by a reduction nitridation method, had an average particle size (D50) of about 1.0 μm, and contained 1% by weight or less of oxygen. As the sintering aid, Y2O3 powder with an average particle size (D50) of about 1.2 μm was used.
[0041] For Examples 1-7, 9-20 and Comparative Examples 1-6, a predetermined amount of Y2O3 powder, about 0.5 parts by weight of a dispersant, and about 60 parts by weight of a mixed solvent of toluene and ethanol were added to 100 parts by weight of aluminum nitride powder, and the mixture was ground and mixed by a ball mill using a resin container and alumina balls. 3.5 parts by weight of an acrylic binder was further added to the ground mixture as a binder, and the mixture was stirred and mixed by a ball mill until the dissolved binder solution and the ground mixture were completely mixed, and then a slurry was produced. Then, the raw material mixture was molded to a predetermined size and thickness by using a press molding method. Specifically, in the press molding method, the mixed and ground slurry was dried and granulated by a spray dryer to obtain AlN granules. Then, the AlN granules were press molded to obtain a substrate-like molded body having a predetermined size and thickness.
[0042] On the other hand, in Example 8, the steps from the mixing step to the molding step are different from those described above in order to form the material using a sheet forming method. A predetermined amount of Y2O3 powder, about 0.8 parts by weight of a surface-active dispersant, and about 25 parts by weight of a mixed solvent of toluene and ethanol were added to 100 parts by weight of aluminum nitride powder, and the mixture was ground and mixed by a ball mill using a resin container and alumina balls. A dissolved binder solution consisting of about 8 parts by weight of polyvinyl butyral as a binder, about 3.5 parts by weight of dibutyl phthalate as a plasticizer, and about 25 parts by weight of a mixed solvent of toluene and ethanol was added to the ground mixture. Then, the dissolved binder solution and the ground mixture were stirred and mixed by a ball mill until they were completely mixed, and then a slurry was prepared. Then, the slurry was heated and left in a vacuum to defoam and volatilize the solvent, and the viscosity at 25°C was adjusted to 20,000 cps. Next, a plate-shaped green sheet was obtained from the prepared slurry by a doctor blade method. The final drying temperature in the doctor blade molding device was set to 120° C. The obtained green sheet was cut into a predetermined size by die pressing to obtain a substrate-like molded product having a predetermined size and thickness.
[0043] Next, the produced molded body was placed in a BN case and heated in a nitrogen atmosphere at about 600°C for 4 hours to perform a degreasing process to remove organic components such as binders. The degreased molded body was placed on a BN bottom plate, and a BN side plate and a top plate were attached to the bottom plate to assemble a closed case. The case containing the molded body was placed in a sintering furnace and heated in a nitrogen atmosphere at 1500 to 1650°C for 10 to 20 hours to perform a deoxidation process for the molded body. For Examples 1 to 20 and Comparative Examples 1 to 4 and 6, the deoxidized molded body was not taken out of the sintering furnace, but was heated in a nitrogen atmosphere at 1750 to 1900°C for 2 to 20 hours to perform a sintering process for the molded body, thereby obtaining an aluminum nitride precursor sintered body. For Comparative Example 5, the sintering process was not performed, and the molded body was taken out of the sintering furnace and proceeded to the next reduction sintering process. For Comparative Example 6, the production of the sample for Comparative Example 6 was completed without proceeding to the next reduction sintering process.
[0044] For Examples 1 to 20 and Comparative Examples 3 to 5, the aluminum nitride precursor sintered body obtained was placed in a graphite container, or a BN container or an AlN container in which carbon black or a carbon sheet was placed, and was embedded in AlN powder for embedding until the aluminum nitride precursor sintered body was no longer visible, as shown in FIG. 1, and was sealed in the BN container or the AlN container. Aluminum nitride powder with an oxygen content of 1% by weight or less was used as the embedding AlN powder in each example. Then, the aluminum nitride precursor sintered body was heated at 1850 to 1950°C for 5 to 100 hours and reduced and fired. In this way, the samples of Examples 1 to 20 and Comparative Examples 3 to 5 were prepared. For Comparative Examples 1 and 2, the aluminum nitride precursor sintered body obtained was placed in a graphite container or a BN container in which carbon black was placed, as shown in FIG. 2, and was sealed in the container. Then, the aluminum nitride precursor sintered body was heated at 1950°C for 70 hours and reduced and fired. In this way, the samples of Comparative Examples 1 and 2 were prepared.
[0045] For each of the prepared samples of Examples 1 to 20 and Comparative Examples 1 to 6, the diffraction patterns obtained by X-ray diffraction measurement and the diffraction peaks of the AlN crystal phase were identified, thereby confirming that an aluminum nitride sintered body was obtained.
[0046] For each of the prepared samples of Examples 1 to 20 and Comparative Examples 1 to 6, various characteristic evaluations were carried out as shown below.
[0047] (i) Thermal conductivity The aluminum nitride sintered body was cut into individual pieces measuring 10 mm × 10 mm × 0.5 mm thick, and a gold sputtering film of about 100 nm was formed on both sides of the individual pieces. Then, graphene was sprayed on both sides of the individual pieces to obtain a graphene coating amount of about 0.1 mg / mm. 2 The samples were subjected to uniform blackening treatment so that the measured values were uniform. A thermal diffusivity measuring device (model LFA467) manufactured by Netsch Japan Co., Ltd. was used to perform measurements three times at a voltage of 250 V and a pulse width of 30 μs, and the average value was taken as the thermal diffusivity. The measured thermal diffusivity was multiplied by the density and specific heat of the sintered body measured by the Archimedes method to obtain the thermal conductivity of the 0.5 mm thick sample. In addition, aluminum nitride sintered bodies have the property that their thermal conductivity decreases when the temperature is high. The laser flash method is a measurement method that calculates the thermal diffusivity from the time it takes for the temperature of the sample to rise, and the measured value includes the decrease in thermal diffusivity due to the increase in the temperature of the sample. If measurements are taken with the same laser intensity, samples with a thinner thickness will have a larger increase in temperature than samples with a thicker thickness, and the thermal diffusivity will be measured as lower. Therefore, the table below shows the data obtained by measuring the thermal diffusivity of a sample with a thickness of 2.5 mmT, and then polishing it to thicknesses of 1.5, 1.0, 0.75, and 0.5 mmT for the same sample. According to Table 1, the thermal conductivity is clearly lower for samples with a thinner thickness. Using the obtained thermal conductivity, the multiplication factor for each thickness was calculated to convert it to a thickness of 2.5 mmT. Specifically, the thermal conductivity value of the sample with 0.5 mmT was multiplied by 1.10 to calculate the thermal conductivity value converted to a thickness of 2.5 mmT. [Table 1]
[0048] (ii) Dielectric constant The aluminum nitride sintered body was cut into individual pieces of 20 mm x 20 mm, and a main electrode of φ16 mm and a guard electrode of φ19 mm were printed on one side using Ag paste (model TR-302XG) manufactured by Tanaka Kikinzoku Kogyo Co., Ltd., and a φ19 mm electrode was printed on the other side. The pieces were then baked at 850°C for 10 minutes in dry air to prepare measurement samples. The capacitance was measured at room temperature at a frequency of 1 MHz using an impedance analyzer (model 4990A) manufactured by Keysight Technologies International, and the relative dielectric constant was calculated from the plate thickness and electrode diameter.
[0049] (iii) Dielectric tangent The pieces used in the dielectric constant measurement were used as measurement samples, and the dielectric loss tangent was measured at room temperature and at a frequency of 1 MHz using an impedance analyzer, model "4990A," manufactured by Keysight Technologies International.
[0050] (iv) Volume resistivity The individual pieces used in the dielectric loss tangent measurement were used as the measurement samples. A digital ultra-high resistance / microammeter, model "5450" manufactured by ADCMT Co., Ltd. was used. A voltage of 1000V was applied at room temperature, and the volume resistance value was obtained after 1 minute of application. The volume resistivity was calculated from the obtained volume resistance value, the plate thickness, and the electrode diameter.
[0051] (v) Dielectric strength The aluminum nitride sintered body was cut into individual pieces of 20 mm x 20 mm to be used as measurement samples. A Fujikura Dia Cable Co., Ltd. partial discharge measurement device, model "A006," was used, and the measurement electrodes on both the top and bottom were φ11 mm, and an AC voltage (sine wave) was applied in a fluorine-based inert liquid (Fluorinert FC-43, manufactured by 3M Japan Co., Ltd.). The AC voltage ramp rate was 500 V / s. The measured dielectric breakdown voltage was divided by the sample thickness to obtain the dielectric strength voltage.
[0052] (vi) Y2O3 content A scanning X-ray fluorescence analyzer, model "Primus IV" manufactured by Rigaku Corporation, was used. The aluminum nitride sintered body produced was cut into a size of 50.8 mm x 50.8 mm, and the Al and Y contents were measured at five points, the center and four corners of the substrate, and the Y2O3 content was calculated using a calibration curve, and the average value was taken as the Y2O3 content.
[0053] (vii) Carbon content The aluminum nitride sintered body thus produced was cut into a size of 50.8 mm x 50.8 mm, and a total of five points, namely the center and four corners of the substrate, were measured using an EMIA-Pro manufactured by Horiba, Ltd., using a high-frequency heating combustion-infrared absorption method in an oxygen stream, and the average value was taken as the carbon content.
[0054] (viii) Lightness L * value The aluminum nitride sintered body thus produced was cut into a size of 50.8 mm x 50.8 mm, and the lightness of the center and four corners of the substrate, a total of five points, was measured using a Konica Minolta color difference meter, model "CR-400," using a diffuse lighting and vertical light receiving method, and the average value of these was calculated as the lightness L. * The values were used. In order to avoid the influence of reflected light from a desk or the like, the board was not placed on the desk or the like during the measurement. Specifically, the color difference meter was held facing upward or sideways, and the board was placed against the measuring part. The light source during the measurement was C.
[0055] Table 2 shows the conditions for each sample of Examples 1 to 20 and Reference Examples 1 to 6 and the results of various measurements regarding the properties of the sintered bodies.
[0056] [Table 2]
[0057] According to Table 2, in Examples 1 to 20 and Comparative Examples 1 and 2, the content of Y2O3 in the sintered body is 0.10% by weight or less, whereas in Comparative Examples 3 to 6, it is 1.5% by weight or more. In particular, in Examples 1 to 13 and 15 to 20, the content of Y2O3 in the sintered body is 0.03% by weight or less, whereas in Example 14, the content of Y2O3 in the sintered body is 0.09% by weight, and in Comparative Examples 1 and 2, the content of Y2O3 in the sintered body is 0.04% by weight or more. The reason why the content of Y2O3 in Example 14 is larger than that in other Examples is that the treatment time (10 hours) of the reduction firing step is shorter than that in other Examples. The content of Y2O3 in Examples 1 to 13 and 15 to 20, which were subjected to reduction firing for 30 hours or more, is smaller than the content of Y2O3 in Comparative Examples 1 and 2, which were subjected to reduction firing for 70 hours without embedding. This shows that the embedding treatment with aluminum nitride powder and reduction firing for 30 hours or more effectively discharges auxiliary components in the sintered body compared to reduction firing without embedding. In addition, the carbon content in the sintered body is 0.05% by weight or less in Examples 1 to 20 and Comparative Examples 3 to 6, whereas the carbon content in the sintered body is 0.08% by weight or more in Comparative Examples 1 and 2. In particular, the carbon content in the sintered body is 0.03% by weight or less in Examples 1 to 20. This shows that the inflow of carbon into the sintered body is suppressed by embedding the precursor sintered body in aluminum nitride powder and reducing and firing it. That is, in Examples 1 to 20, the content of Y2O3 in the sintered body was controlled to 0.10% by weight or less, and the carbon content in the sintered body was controlled to 0.05% by weight or less.
[0058] In Examples 1 to 20 and Comparative Examples 1 to 3, the thermal conductivity (2.5T conversion) is high, at 240 W / mK or more, whereas in Comparative Examples 4 to 6, the thermal conductivity (2.5T conversion) is 231 W / mK or less. This is because Comparative Examples 4 and 6 did not undergo an appropriate reduction firing process, and therefore auxiliary components were not sufficiently discharged. Also, in Comparative Example 5, this is because a sintering process was not performed.
[0059] In Examples 1 to 20, L * In contrast, in Comparative Examples 1 to 6, the L *In particular, in Comparative Examples 1 and 2 without embedding, the L * The value is 51 or less. This shows that the appearance of the aluminum nitride sintered body substrate differs depending on whether or not it is embedded in the reduction firing process.
[0060] Next, Table 3 shows the conditions for each sample of Examples 1 to 20 and Comparative Examples 1 to 6 and the results of various measurements regarding the electrical properties of the sintered bodies.
[0061] [Table 3]
[0062] According to Table 3, in Examples 1 to 20 and Comparative Examples 1, 2, and 6, the relative dielectric constant is 8.5 or less and the dielectric dissipation factor is 0.001 or less, whereas in Comparative Examples 3 to 5, the relative dielectric constant is greater than 8.5 and the dielectric dissipation factor is greater than 0.001.
[0063] In Examples 1 to 20, the volume resistivity was 5.0 × 10 13 Ω·cm or more, whereas in Comparative Examples 1 to 6, the volume resistivity was 3.6×10 13 Ω·cm or less. That is, Examples 1 to 20 have high electrical insulation properties as an insulating material compared to Comparative Examples 1 to 6. And, in Examples 1 to 20, the dielectric strength is 20 kV / mm or more, whereas in Comparative Examples 1 to 6, the dielectric strength is 17 or less. In particular, Examples 1 to 20 have a dielectric strength of 23 kV / mm or more. In contrast, Comparative Examples 1 to 3, which have a high thermal conductivity of 240 W / mK or more (2.5 T conversion), have a dielectric strength of 11 kV / mm or less. That is, Examples 1 to 20 have a thermal conductivity of 240 W / mK or more (2.5 T conversion) and a dielectric strength of 20 kV / mm or more, and therefore, they achieve both high thermal conductivity and high insulating performance.
[0064] Dielectric strength and L * When the values of insulation voltage and L were plotted on a graph, a correlation was obtained between the two, as shown in Figure 3. * It is linearly proportional to the value of L* It was found that a value of 57 or higher meets the requirement of at least a dielectric strength of 20 kV / mm or more.
[0065] That is, by introducing an embedding process of aluminum nitride powder into the reduction firing step, the aluminum nitride sintered body of the present invention has a Y2O3 content controlled to 0.10% by weight or less and a carbon content controlled to 0.05% by weight or less. As a result, the aluminum nitride sintered body of the present invention has a high thermal conductivity of 240 W / mK or more (2.5 T conversion) and high electrical properties (dielectric strength of 20 kV / mm or more and / or a dielectric strength of 5.0×10 13 It is a material that satisfies both the requirements for a high-temperature resistance and a volume resistivity of 0.1 Ω·cm or more.
[0066] The present invention is not limited to the above-described embodiment, and can be embodied in various forms within the technical scope of the present invention. [Explanation of symbols]
[0067] 10. Electronic Components 11 Aluminum nitride sintered substrate 13 Laser Diode 15 Heat sink 17 Conductive Film
Claims
1. An aluminum nitride sintered body comprising aluminum nitride particles and a sintering aid phase, The thermal conductivity when converted to a thickness of 2.5 mm is 240 W / mK or more, Y in the sintered body 2 O 3 1. An aluminum nitride sintered body, comprising: an aluminum nitride sintered body having a carbon content of 0.1% by weight or less; and a carbon content of 0.05% by weight or less in the sintered body.
2. 2. The aluminum nitride sintered body according to claim 1, characterized in that the carbon content in the sintered body is 0.03% by weight or less.
3. 2. The aluminum nitride sintered body according to claim 1, characterized in that the dielectric strength voltage is 20 kV / mm or more.
4. Volume resistivity is 5.0×10 13 2. The aluminum nitride sintered body according to claim 1, characterized in that it has a resistivity of Ω·cm or more.
5. 2. The aluminum nitride sintered body according to claim 1, wherein the aluminum nitride sintered body has a relative dielectric constant of 8.5 or less and a dielectric loss tangent of 0.001 or less.
6. In the substrate of the aluminum nitride sintered body, the average value of the brightness measured at one point in the center and four points at the corners is L * 2. The aluminum nitride sintered body according to claim 1, characterized in that the value is 57 or more.
7. 7. An electronic component comprising: the aluminum nitride sintered body according to claim 1; and a laser diode mounted on a surface of the aluminum nitride sintered body.
Citation Information
Patent Citations
Aluminum nitride sintered body
JP1988002860A
Production of aluminum nitride sintered compact
JP1991137059A
Silicon nitride-based sintered compact and its production
JP1994128041A
Aluminum nitride base sintered compact, its production and susceptor using the same
JP2000327424A
Aluminium nitride sintered compact and method for producing the same
JP2002037670A